A one-step rapid screening test of Listeria monocytogenes in food samples using a real-time loop-mediated isothermal amplification turbidity assay. Issue 45 (9th November 2017) - Wachiralurpan, Sirirat; Sriyapai, Thayat; Areekit, Supatra; Sriyapai, Pichapak; Thongphueak, Dueantem; Santiwatanakul, Somchai; Chansiri, Kosum
Abstract : A rapid and specific, hly -based, loop-mediated isothermal amplification (LAMP) was applied for the detection of Listeria monocytogenes in food samples using LAMP-turbidity. Abstract : A rapid and specific, hly -based, loop-mediated isothermal amplification (LAMP) was applied for the detection of Listeria monocytogenes in food and food products, using a real-time turbidimeter platform (LAMP-turbidity). The principle behind this method relies on an increase in a DNA yield, which correlates with the production of magnesium pyrophosphate, and the results can be determined via an amplification curve within 1 h. The specificity test revealed that L. monocytogenes (DMST 17303) was observed from 34.1 to 38.3 min, while thirty strains of non- L. monocytogenes demonstrated no cross-reactions. The limits of detection for purified genomic DNA and pure culture were 800 pg μL −1 and 2.82 × 10 3 CFU mL −1, respectively. Investigation on 200 raw chicken meat samples indicated that the specificity, sensitivity, and accuracy of LAMP-turbidity were 100%, 62.75%, and 90.50%, respectively. These data suggest that an hly -based, real-time, quantitative LAMP-turbidity assay can be an applicable tool for the epidemiological screening of L. monocytogenes in food and food products.